CRISPR/Cas9-targeted enrichment and long-read sequencing of the Fuchs endothelial corneal dystrophy-associated TCF4 triplet repeat - Hafford-Tear, Nathaniel J; Tsai, Yu-Chih; Sadan, Amanda N; Sanchez-Pintado, Beatriz; Zarouchlioti, Christina; Maher, Geoffrey J; Liskova, Petra; Tuft, Stephen J; Hardcastle, Alison J; Clark, Tyson A; Davidson, Alice E (Genetics in medicine, 2019)
PURPOSE: To demonstrate the utility of an amplification-free long-read sequencing method to characterize the Fuchs endothelial corneal dystrophy (FECD)-associated intronic TCF4 triplet repeat (CTG18.1). METHODS: We applied an amplification-free method, utilizing the CRISPR/Cas9 system, in combination with PacBio single-molecule real-time (SMRT) long-read sequencing, to study CTG18.1. FECD patient samples displaying a diverse range of CTG18.1 allele lengths and zygosity status (n = 11) were analyzed. A robust data analysis pipeline was developed to effectively filter, align, and interrogate CTG18.1-specific reads. All results were compared with conventional polymerase chain reaction (PCR)-based fragment analysis. RESULTS: CRISPR-guided SMRT sequencing of CTG18.1 provided accurate genotyping information for all samples and phasing was possible for 18/22 alleles sequenced. Repeat length instability was observed for all expanded (≥50 repeats) phased CTG18.1 alleles analyzed. Furthermore, higher levels of repeat instability were associated with increased CTG18.1 allele length (mode length ≥91 repeats) indicating that expanded alleles behave dynamically. CONCLUSION: CRISPR-guided SMRT sequencing of CTG18.1 has revealed novel insights into CTG18.1 length instability. Furthermore, this study provides a framework to improve the molecular diagnostic accuracy for CTG18.1-mediated FECD, which we anticipate will become increasingly important as gene-directed therapies are developed for this common age-related and sight threatening disease.
Keywords: dospělí; Genotype; Female; Transcription Factor 4; CRISPR-Cas systémy; Adult; ženské pohlaví; expanze trinukleotidových repetic; CRISPR-Cas Systems; Single Molecule Imaging; introny; lidé; transkripční faktor 4; genotyp; Introns; genetická predispozice k nemoci; Aged, 80 and over; Genetic Predisposition to Disease; zobrazení jednotlivé molekuly; Fuchsova endoteliální dystrofie; trinukleotidové repetice; Middle Aged; Male; Aged; Trinucleotide Repeat Expansion; alely; Sequence Analysis, DNA; Alleles; Trinucleotide Repeats; lidé středního věku; senioři nad 80 let; senioři; mužské pohlaví; sekvenční analýza DNA; Fuchs' Endothelial Dystrophy; Humans